Mcgraw-hill education conquering gre math, fourth edition. - Moyer, Robert E (New York : McGraw-Hill Education, 2020)
The Quantitative section of the GRE is extremely challenging, so we're here to help. Conquering GRE Math --covering the latest test formula -- has been specially designed by a test-prep expert to give you strategies for solving every kind of GRE math question. You'll also get intensive practice for every question type to help your test-taking confidence. With Conquering GRE Math, you'll have everything you need to get ready for test day, and achieve your best GRE math score.
The GRE quantitative reasoning sections -- The mathematics you need to review -- Calculators on the GRE quantitative reasoning sections -- GRE quantitative comparison questions -- GRE multiple-choice questions -- Other GRE math question formats -- GRE date interpretation questions -- Number properties -- Arithmetic computation -- Algebra -- Geometry -- GRE math practice sections.
Keywords: Graduate record examination -- Guides de l'étudiant.; Graduate Record Examination -- Study guides; Mathematics -- Examinations, questions, etc; Universities and colleges -- Graduate work -- Examinations -- Study guides